2017
DOI: 10.1002/admt.201700210
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Tattoo Patch for Ultrasound‐Based Transdermal Microballistic Delivery

Abstract: patch technology has led to significant surge in first-generation transdermal patches. [19][20][21][22] The marriage between effective needle-free delivery platforms and wearable devices could thus prove highly desirable. However, achieving the desired therapeutic or detoxification effect requires further attention to the low permeability of the human skin.Herein, we present a flexible epidermal tattoo patch, containing thousands of microcannons, for efficient ultrasoundtriggered microballistic transdermal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Figure Ai displays a schematic of the OPH‐modified microbead attached to the rotibot. Electrochemical square‐wave voltammetry (SWV) technique was used to measure the nitro‐phenolic byproduct of the OPH enzyme hydrolyzation of methyl paraoxon . The voltammograms in Figure Aii represent different incubation conditions with a methyl paraoxon solution, including a) negative control, b) bare rotifers, c) static OPH–microbeads, and (d) OPH‐modified rotibots.…”
Section: Resultsmentioning
confidence: 99%
“…Figure Ai displays a schematic of the OPH‐modified microbead attached to the rotibot. Electrochemical square‐wave voltammetry (SWV) technique was used to measure the nitro‐phenolic byproduct of the OPH enzyme hydrolyzation of methyl paraoxon . The voltammograms in Figure Aii represent different incubation conditions with a methyl paraoxon solution, including a) negative control, b) bare rotifers, c) static OPH–microbeads, and (d) OPH‐modified rotibots.…”
Section: Resultsmentioning
confidence: 99%
“…Wang and coworkers, on the other hand, have used membranes with 12 µm conical pores and they loaded these pores with silica particles and phase-change droplets 225. They showed that vaporization of phase-change droplets using FUS fired the silica nanoparticles from these “microcannons,” which could be useful for transdermal delivery (Figure 14) 226. Later they also used this strategy for transdermal delivery of an anesthetic agent lidocaine 227.…”
Section: Acoustically Active Materials For Fus Theranosticsmentioning
confidence: 99%
“…C) Schematic showing drug delivery by vaporization of fluorocarbon droplets. Adapted from reference 226 copyright 2017 Wiley-VCH.…”
Section: Figurementioning
confidence: 99%
“…Moreover, unlike microneedle delivery devices that require to pierce the skin interface, our system achieves enhanced drug permeability through a nonpenetrative highly localized stress force produced by the ADV mechanism and suggests a potential nonimmunogenic method of delivery. The ability of ADV to deliver large microparticles from microporous membranes has been demonstrated earlier toward enhanced decontamination processes. Finally, we demonstrate the preclinical utility of the wearable patch through enhanced delivery and penetration of lidocaine in ex‐vivo pigskin model (a model that simulates human skin), as well as achieving high delivery efficacy at significantly shorter periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound-triggered vaporization of the PFC compound [38][39][40][41] provides the necessary force to enhance significantly skin penetration and delivery of drug payloads when compared to common systems based solely on passive diffusion or ultrasound pulses.Moreover, unlike microneedle delivery devices that require to pierce the skin interface, our system achieves enhanced drug permeability through a nonpenetrative highly localized stress force produced by the ADV mechanism and suggests a potential nonimmunogenic method of delivery. The ability of ADV to deliver large microparticles from microporous membranes [42,43] has been demonstrated earlier toward Current technologies for managing acute and chronic pain have focused on reducing the time required for achieving high therapeutic efficiency. Herein a wearable transdermal patch is introduced, employing an acoustic droplet vaporization (ADV) methodology, as an effective noninvasive transdermal platform, for a fast local delivery of the anesthetic agent lidocaine.…”
mentioning
confidence: 99%